2020
DOI: 10.1186/s12881-020-01115-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations of NOD2 polymorphisms with Erysipelotrichaceae in stool of in healthy first degree relatives of Crohn’s disease subjects

Abstract: Background Genetic analyses have identified many variants associated with the risk of inflammatory bowel disease (IBD) development. Among these variants, the ones located within the NOD2 gene have the highest odds ratio of all IBD genetic risk variants. Also, patients with Crohn’s disease (CD) have been shown to have an altered gut microbiome, which might be a reflection of inflammation itself or an effect of other parameters that contribute to the risk of the disease. Since NOD2 is an intracellular pattern re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…Indeed, our results showed that the relative abundance of norank_Erysipelotrichaceae was positively correlated with the genes encoded IgA. This taxon can produce palmitic, stearic, oleic acid, and fatty acids, which could result in metabolism disorder, stimulate pro-inflammatory cytokine production and enhance the responses of T helper 17 cells (76,77). In the present study, the relative abundance of norank_f_Erysipelotrichaceae was significantly enriched with HFD, which was consistent with the previous report (78).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, our results showed that the relative abundance of norank_Erysipelotrichaceae was positively correlated with the genes encoded IgA. This taxon can produce palmitic, stearic, oleic acid, and fatty acids, which could result in metabolism disorder, stimulate pro-inflammatory cytokine production and enhance the responses of T helper 17 cells (76,77). In the present study, the relative abundance of norank_f_Erysipelotrichaceae was significantly enriched with HFD, which was consistent with the previous report (78).…”
Section: Discussionsupporting
confidence: 92%
“…Certain Bacteroides species are considered biomarkers of IBD and their associated OmpW proteins can be used as targets for developing IBD immunotherapy ( 29 ). Shigella and Erysipelotrichaceae are considered opportunistic pathogens in the human gut and are significantly increased in Crohn’s disease ( 30 , 31 ). Erysipelotrichaceae can produce phenyl sulfate, which impairs glomerular function and is highly associated with diabetic nephropathy ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, it is interesting to note that a recent study by Turpin et al 32 , being specifically targeted at NOD2 , demonstrated an association between variants in this gene and the fecal microbiome composition in healthy first-degree relatives of CD patients. Notably, the authors also pointed out the advantages of their study design over traditional association studies of population-representative healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the authors also pointed out the advantages of their study design over traditional association studies of population-representative healthy individuals. In contrast to Turpin et al 32 however, our study (i) was not focused upon certain genetic variants, but covered all genomic regions implicated in IBD by GWAS before, and (ii) used a genetic linkage approach in IBD families to explore the possible joint role of genotype and microbiome in the etiology of the disease.…”
Section: Discussionmentioning
confidence: 99%